Epigenetic signatures of Werner syndrome occur early in life and are distinct from normal epigenetic aging processes. Issue 5 (1st July 2019) - Maierhofer, Anna; Flunkert, Julia; Oshima, Junko; Martin, George M.; Poot, Martin; Nanda, Indrajit; Dittrich, Marcus; Müller, Tobias; Haaf, Thomas
Abstract: Werner Syndrome (WS) is an adult‐onset segmental progeroid syndrome. Bisulfite pyrosequencing of repetitive DNA families revealed comparable blood DNA methylation levels between classical (18 WRN ‐mutant) or atypical WS (3 LMNA ‐mutant and 3 POLD1 ‐mutant) patients and age‐ and sex‐matched controls. WS was not associated with either age‐related accelerated global losses of ALU, LINE1, and α‐satellite DNA methylations or gains of rDNA methylation. Single CpG methylation was analyzed with Infinium MethylationEPIC arrays. In a correspondence analysis, atypical WS samples clustered together with the controls and were clearly separated from classical WS, consistent with distinct epigenetic pathologies. In classical WS, we identified 659 differentially methylated regions (DMRs) comprising 3, 656 CpG sites and 613 RefSeq genes. The top DMR was located in the HOXA4 promoter. Additional DMR genes included LMNA, POLD1, and 132 genes which have been reported to be differentially expressed in WRN ‐mutant/depleted cells. DMRs were enriched in genes with molecular functions linked to transcription factor activity and sequence‐specific DNA binding to promoters transcribed by RNA polymerase II. We propose that transcriptional misregulation of downstream genes by the absence of WRN protein contributes to the variable premature aging phenotypes of WS. There were no CpG sites showing significant differences in DNA methylation changes with age between WS patients and controls. Genes with both WS‐ and age‐related methylation changes exhibited a constant offset of methylation between WRN ‐mutant patients and controls across the entire analyzed age range. WS‐specific epigenetic signatures occur early in life and do not simply reflect an acceleration of normal epigenetic aging processes. Abstract : Werner syndrome (WS) is not associated with an acceleration of normal epigenetic aging processes, but rather with hypermethylation and less frequently hypomethylation of specific subsets of genes early in life. This epigenetic misregulation of downstream genes transcribed by RNA polymerase II may contribute to disease onset and premature aging symptoms. Epigenetic signatures largely differ between classical and atypical WS patients, consistent with distinct epigenetic pathologies.